Do State Ownership and Business Environment Explain Corporate Cash Holdings? Empirical Evidence from An Emerging Country - Tran Thai Ha Nguyen; Wing-Keung Wong (Asian Academy of Management Journal of Accounting and Finance, 2021)
This study evaluates the relationship between state ownership and corporate cash holdings by taking into account the role of the business environment in the context of an emerging economy. Both linear and non-linear models are employed for listed enterprises’ financial data during the period from 2011 to 2019 in Vietnam. The empirical results show that state ownership reduces the corporate cash holdings in the linear model, and there is a U-shaped relation between corporate cash holdings and state ownership in a non-linear manner. By using the extended models, this study obtains consistent evidence to show that corporates reduce their cash holdings when the business environment becomes better and vice versa. Specifically, we find that the speed of cash adjustment in Vietnam is smaller than that in the developed countries, implying that corporates can shelter their liquid assets in order to avoid the negative effects stemming from agency problems between managers and state-shareholders. However, they are willing to hold more cash because of the mitigated agency problems in the case of the dominant state ownership. Ultimately, the business environment’s quality will have more power in determining the behaviour of corporates’ cash holding to meet market risks than state ownership. This study contributes to financial literature by determining the business environment’s critical role in the relationship between state ownership and corporate cash holdings.